2013
DOI: 10.20360/g22g66
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and opportunities for literacy teaching: A case study of primary core French classrooms in Ontario.

Abstract: Increasingly, Canadian educators are being told that literacy development can occur across subject areas of the curriculum. Few studies have focused on whether this applies to core French as a second language (CF). This article reports on a mixed method case study investigating the literacy teaching practices and accompanying influential factors of one Ontario primary core French teacher whose activities, strategies and perspectives demonstrate the potential for CF instruction to echo literacy principles taugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…For example, observations by Simard and Jean (2011) showed that grammar-oriented interventions are a dominant part of FSL teaching when compared to English as a second language (ESL) teaching in the Canadian context (in this case, Quebec). Precise ways in which both CF and FI teachers can capitalize on students' existing language knowledge in order to promote transfer between languages have also been described in detail (Arnott & Mady, 2013;Cammarata & Haley, 2017;Thomas & Mady, 2014;Vandergrift, 2006). Researchers have used these findings to make suggestions about what is indeed pedagogically possible (or not) in the K-12 FSL context.…”
Section: French Language Instruction (Fli)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, observations by Simard and Jean (2011) showed that grammar-oriented interventions are a dominant part of FSL teaching when compared to English as a second language (ESL) teaching in the Canadian context (in this case, Quebec). Precise ways in which both CF and FI teachers can capitalize on students' existing language knowledge in order to promote transfer between languages have also been described in detail (Arnott & Mady, 2013;Cammarata & Haley, 2017;Thomas & Mady, 2014;Vandergrift, 2006). Researchers have used these findings to make suggestions about what is indeed pedagogically possible (or not) in the K-12 FSL context.…”
Section: French Language Instruction (Fli)mentioning
confidence: 99%
“…Setting aside the impact of pedagogy on student learning, a smaller proportion of the studies documenting FSL teacher practices included a complementary analysis of teacher perspectives on their FSL pedagogy, which offered additional explanations for what the researchers had observed. For example, interviews revealed that CF teachers specifically plan for transfer (Thomas & Mady, 2014) and that collaboration and coplanning are key to implementing literacy-based practices in this context (Arnott & Mady, 2013). Other researchers used interviews to conclude that teacher beliefs had a major influence on the FSL teacher practices that were observed (e.g., Arnett, 2010;Arnott, 2011).…”
Section: French Language Instruction (Fli)mentioning
confidence: 99%
“…
The fundamental knowledge base of effective vocabulary teaching and learning includes the extensive body of research on vocabulary instruction methods and the process of language acquisition. This knowledge base also includes the current understanding of issues and constraints of literacy instruction in language classrooms (Arnott & Mady, 2013). Research in the past has increased the depth of understanding issues related to vocabulary, including the nature of word knowledge, pedagogy for developing vocabulary acquisition, and the complex issues between vocabulary and comprehension (Fernandes, Querido, Verhaeghe, Marques, & Araújo, 2017).Research has also shed light upon effective instructional practices for teaching vocabulary.
…”
mentioning
confidence: 99%
“…In planning for transfer, L2 teachers can compare curricula for different languages with an eye toward creating learning experiences to activate prior knowledge mediated in any language (Cummins, 2008) and create new connections. This potential for cross-linguistic transfer points to a redefinition of the CF teacher as a literacy teacher, and thus as a contributor to a school's literacy team (see Arnott & Mady, 2013).…”
mentioning
confidence: 99%